Module for adaptative teaching planning for a tutoring system - Ceyca Ceyca, Jorge Omar (2007)
The teaching process has been strengthened by the emergence of modern computer technologies, which have permitted developing distance education mainly through the use of the Internet. In this field tutoring systems have become one the most benefited and important tools for teaching. However, adapting tutoring systems to students’ capacity is one the issues that has just begun being explored [1, 2]. This paper describes a module for adaptive teaching planning for a tutoring system that is under development [3, 4]. This module modifies the teaching contents depending on the estimation of two of students’ cognitive abilities: memorization and comprehension.